Epistemic Uncertainties in Climate Predictions: A Challenge for Practical Decision Making - Rafaela Hillerbrand (Intergenerational Justice Review)
Most scientists agree that, at least for the time being, unquantified uncertainties are inevitably connected to predictions of climate models. Uncertainties, however, do not justify political inaction. This paper addresses the question of how epistemic uncertainties are of relevance for practical decision making. It is shown how common decision approaches based on the precautionary principle fail to adequately deal with uncertainties as they arise in climate modeling. I argue that with regards to climate change, unquantified uncertainties can neither be ignored in decision making nor be reduced to quantified ones by assigning subjective probabilities. This distinguishes the ethical problems associated with climate change from other problems regarding energy supply and demand like, for example, those associated with nuclear power.